Issues in Energy Optimization of Reinforcement Learning Based Routing Algorithm Applied to Ad-hoc Networks - Kulkarni, S.A.; Rao, G.R. (Informatica)
Issues in Energy Optimization of Reinforcement Learning Based Routing Algorithm Applied to Ad-hoc Networks